Induction of the POU domain transcription factor Oct-2 during T-cell activation by cognate antigen. - Kang, S M (1992)
Oct-2 is a transcription factor that binds specifically to octamer DNA motifs in the promoters of immunoglobulin and interleukin-2 genes. All tumor cell lines from the B-cell lineage and a few from the T-cell lineage express Oct-2. To address the role of Oct-2 in the T-cell lineage, we studied the expression of Oct-2 mRNA and protein in nontransformed human and mouse T cells. Oct-2 was found in CD4+ and CD8+ T cells prepared from human peripheral blood and in mouse lymph node T cells. In a T-cell clone specific for pigeon cytochrome c in the context of I-Ek, Oct-2 was induced by antigen stimulation, with the increase in Oct-2 protein seen first at 3 h after activation and continuing for at least 24 h. Oct-2 mRNA induction during antigen-driven T-cell activation was blocked by cyclosporin A, as well as by protein synthesis inhibitors. These results suggest that Oct-2 participates in transcriptional regulation during T-cell activation. The relatively delayed kinetics of Oct-2 induction suggests that Oct-2 mediates the changes in gene expression which occur many hours or days following antigen stimulation of T lymphocytes.